What's the buzz: Tell me what's happening in breast cancer screening - Sharon K Byrne (Elsevier, 2017)
Many controversies have come to light related to breast cancer screening recommendations for average- and high-risk populations. This manuscript focuses on factors to consider when coordinating and conducting breast cancer screening programs in an average or "healthy women" population. As presented at the 2016 ONS Congress, a brief comparison of current screening recommendations among various organizations for early detection of breast cancer is provided. Lessons learned regarding key components of successful screening programs such as being patient focused, accessible, and sustainable are shared. Practice implications such as gaining confidence in providing individualized patient education, encouraging every woman to discuss her risk of breast cancer with her health-care provider, advocating for patients needs and being involved in or aware of clinical and translational research on the efficacy of the clinical breast examination and screening services are critical roles for nurses and advanced practice nurse providers.